Developing Communicative Competence of Future Teachers on the Basis of Ethnic and Cultural Values Intrinsic to Highlanders of the Ukrainian Carpathians - Stakhiv, Maria (Journal of Vasyl Stefanyk Precarpathian National University, 2014)
The article presents challenges and methods of teacher training activities aimed to develop communicative competence and prepare teachers for work in mountain area schools in the Ukrainian Carpathians. Research shows that specifics of social and cultural environment should be taken into account in the process of teaching native language and developing communicative competence of future teachers. Sociocultural approach defines language teaching strategies in the light of national culture, traditions of ethnic regions and the Ukrainian Carpathians in particular. Teacher training programs should include studies on material, cultural and spiritual values of highlanders. Such topics can be incorporated in the main native language course. Study and analysis of fiction pieces, especially those that reflect the socio-cultural peculiarities of linguistic community of the Ukrainian Carpathians can be of great value in achieving the goal. Small classes in mountain schools also place a demand upon educators to constantly upgrade approaches, forms and methods of teaching. The article offers an integral teacher training system aimed at developing communicative competence and preparing teachers to work in the mountain areas schools. A special place in this system is given to folk pedagogy, which accumulates the national and regional spiritual values. The author presents the components of communicative and socio-cultural competence of future teachers. The suggested algorithm for training primary school teachers insures reaching an appropriate level of socio-cultural, historical, linguistic and communicative competencies necessary for language teaching at primary schools in mountain regions of the Ukrainian Carpathians.